Climate change impacts on the coral reefs of the UK Overseas Territory of the Pitcairn Islands: resilience and adaptation considerations. (November 2022) - Lincoln, Susana; Cowburn, Benjamin; Howes, Ella L.; Birchenough, Silvana; Pinnegar, John K.; Dye, Stephen; Buckley, Paul; Sheppard, Charles; Wabnitz, Colette C.C.; Dutra, Leo X.C.; Graham, Jennifer; Archer-Rand, Simeon; et al.
Abstract: The coral reefs of the Pitcairn Islands are in one of the most remote areas of the Pacific Ocean, and yet they are exposed to the impacts of anthropogenic climate change. The Pitcairn Islands Marine Protected Area was designated in 2016 and is one of the largest in the world, but the marine environment around these highly isolated islands remains poorly documented. Evidence collated here indicates that while the Pitcairn Islands' reefs have thus far been relatively sheltered from the effect of warming sea temperatures, there is substantial risk of future coral decalcification due to ocean acidification. The projected acceleration in the rate of sea level rise, and the reefs' exposure to risks from distant ocean swells and cold-water intrusions, add further uncertainty as to whether these islands and their reefs will continue to adapt and persist into the future. Coordinated action within the context of the Pitcairn Islands Marine Protected Area can help enhance the resilience of the reefs in the Pitcairn Islands. Options include management of other human pressures, control of invasive species and active reef interventions. More research, however, is needed in order to better assess what are the most appropriate and feasible options to protect these reefs.